Rate Pressure Product Responses during an Acute Session of Isometric Resistance Training: A Randomized Trial - Debra J. Carlson; James R. McFarlane; Gudrun Dieberg; Neil A. Smart (Journal of Hypertension and Cardiology, 2017)
Hypertension is a major modifiable risk factor for cardiovascular disease, responsible for approximately 31% of global mortality. The aim of this study was to examine the hypertensive responses and determine the peak rate pressure product, calculated by multiplying systolic blood pressure and heart rate, during isometric handgrip exercise. Rate pressure product is a surrogate measure of myocardial oxygen consumption. Hypertensive responses utilising rate pressure product during isometric handgrip exercise have not previously been reported. A randomized trial was conducted with 60 normotensive and 60 pre-hypertensive participants who attended once for an acute session of isometric handgrip exercise. Participants were randomized into groups exercising at 5%, 10% or 30% of their maximum voluntary contraction. Training was conducted using 4x2min isometric handgrip exercises each separated by a 3min rest period. There were no significant differences between peak systolic and diastolic blood pressure, mean arterial pressure, heart rate and rate pressure product across the four bouts of isometric handgrip exercise in all groups, all p>.05. Peak increases in rate pressure product were significantly higher than baseline at all intensities assessed; all normotensive groups p<.02, all pre-hypertensive groups p≤.001. Increases were relative to baseline blood pressure status and intensity of isometric handgrip exercise, with no significant differences between normotensive and pre-hypertensive groups. Rate pressure product responses to isometric handgrip exercise indicate that it may be a safe alternative for people unable to perform recommended levels of aerobic exercise for blood pressure management.
Keywords: Isometric exercise